2020
DOI: 10.1007/s00167-020-05929-2
|View full text |Cite
|
Sign up to set email alerts
|

Meniscoplasty leads to good mid-term to long-term outcomes for children and adolescents with discoid lateral meniscus

Abstract: PurposeTo date, there have been limited studies reporting the mid‐ to long‐term outcomes of meniscoplasties for discoid lateral meniscus. The current study aims to evaluate the mid‐ to long‐term outcomes of arthroscopic meniscoplasty for discoid lateral meniscus in children and adolescents. MethodsIn the study, all patients under the age of 21 years who had undergone arthroscopic meniscoplasty with or without meniscal repair or partial meniscectomy for symptomatic lateral discoid meniscus were included. All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 22 publications
2
50
0
2
Order By: Relevance
“…Wong et al [28] concluded that there was no significant difference in the postoperative outcomes among these three surgical methods. Some studies have found no difference between meniscoplasty and total meniscectomy as to shortterm clinical outcomes [36][37][38], but the clinical efficacy of meniscoplasty is better than that of total meniscectomy in the long-term follow-up [3,24,[38][39][40][41][42]. Other studies have shown that the long-term outcomes of meniscoplasty with or without repair are satisfactory, without statistical difference [9,38,39,41,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al [28] concluded that there was no significant difference in the postoperative outcomes among these three surgical methods. Some studies have found no difference between meniscoplasty and total meniscectomy as to shortterm clinical outcomes [36][37][38], but the clinical efficacy of meniscoplasty is better than that of total meniscectomy in the long-term follow-up [3,24,[38][39][40][41][42]. Other studies have shown that the long-term outcomes of meniscoplasty with or without repair are satisfactory, without statistical difference [9,38,39,41,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…As a general rule, preservation of as much meniscal tissue as possible is preferred for long-term joint health, thus repair should be considered as a first option. 2 , 6 , 8 , 9 , 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 Standard treatment includes arthroscopic saucerization and repair/stabilization, as needed. 2 , 8 , 9 , 10 When intrasubstance degeneration (ID) is present, it is often not seen until near completion of saucerization because of its presence on the outer portion of the meniscus. The meniscus will typically split into a superior and inferior leaflet, and the decision has to be made to repair them or resect one or both based on intraoperative assessment of thickness and tissue quality.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, open surgery was the only solution to improve the shape and function of the meniscus. However, with the wide application of arthroscopy, treatment with minimal invasion has become the current mainstream treatment for discoid meniscus (9). Studies have shown that with arthroscopy, a clear diagnosis, small trauma, quick postoperative recovery, and low incidence of complications such as infection can be achieved (10).…”
Section: Discussionmentioning
confidence: 99%